THES STUDY OF ETHANOLIC EXTRACT OF BINAHONG LEAVES (ANREDERA CORDIFOLIA (TEN.) STEENIS) AND MULBERRY LEAVES (MORUS NIGRA L.) IN COMBINATION ON HYPERLIPIDEMIC INDUCED RATS - Sukandar, Elin Yulinah; Safitri, Dewi; Aini, Nisrina Nur (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: This study aimed to determine antihyperlipidemic activity of binahong leaves and murbey leaves extracts in combination. Methods: A total of 28 rats were divided into seven groups: normal, control, simvastatin 3.6 mg/kg bw, binahong leaves extract 100 mg/kg bw (B100), mulberry leaves extract 200 mg/kg bw (M200), combination of binahong extract 50 mg/kg and mulberry 100 mg/kg (B50+M100), and combination of binahong extract 100 mg/kg bw and mulberry 200 mg/kg bw (B100+M200). Hyperlipidemia was induced by giving rats a high fat diet along with cholesterol (200 mg/kg), cholic acid (0.2% of chow), and propylthiouracil (10 mg/kg bw) for 30 days orally. Then, for the next 14 days, all groups except the control were given the tested substances. Measurement of lipid profile was performed immediately after induction (T0), seven and fourteen days after treatment (T7 and T14, respectively). Results: There were significant differences on a group of M200, B50+M100, and B100+M200 compared to the control group at T14, with the value 33.68%, 34.39 %, and 44.81% (in reduction of total cholesterol) and 36.86%, 37.16%, and 49.99% (in reduction of triglyceride). Conclusion: Group of M200, B50+M100, and B100+M200 reduced total cholesterol and triglyceride level remarkably at day 14. The combination of both extract (B100+M200) considerably shows better activity than either binahong extract or mulberry extract.Â